Reformasi Pendidikan Islam melalui Integrasi Epistemologi: Studi Kasus Kurikulum STEAM Pondok Pesantren Athaya - Albert Taqy As Syakur; Akbar Yusgiantara; Mita Nur Khasanah; Baidi Baidi (Lembaga Yasin AlSys, 2025)
Modern Islamic education faces a critical challenge in the form of an epistemic conflict between religious and secular knowledge, which threatens the integrity of the Islamic education system. This study aims to examine the application of Amin Abdullah’s integration-interconnection paradigm in the educational practices of Pondok Pesantren Athaya Solo and its significance for the reform of Islamic education in Indonesia. Employing a qualitative method with an instrumental case study approach, data were collected through comprehensive interviews, participatory observation, and curriculum document analysis. The data were analyzed through interactive stages of data reduction, data display, and conclusion drawing. The findings reveal that Pondok Pesantren Athaya has successfully integrated three curricular pillars, Civic Education (Kebangsaan), Religious Studies (Dinniyah), and STEAM into a single educational framework grounded in Islamic values and knowledge. Project-based learning, the reinforcement of spiritual values, and a trilingual approach serve as key elements in bridging religious and scientific knowledge. Character development through contextual activities demonstrates the effectiveness of this integrative approach in enhancing students’ academic, ethical, and spiritual competencies. The study concludes that the integration-interconnection paradigm can be effectively implemented within the context of Islamic-based secondary education. The Athaya model offers a strategic reference for national Islamic education reform aimed at overcoming the dichotomy between modern science and religious belief.